In Vitro Interactions of Antifungal Agents and Everolimus Against Aspergillus Species - Jiang, Huiping; Xiong, Jianqun; Tan, Lihua; Jin, Ping; Sun, Yi; Yang, Lianjuan; Tan, Jingwen (Frontiers in Cellular and Infection Microbiology, 2022)
Multiple cellular activities, including protein and lipid synthesis, ribosome biogenesis, and metabolic processes, are regulated by the target of the rapamycin (TOR) pathway. Recent research suggests that TOR may play an important role in various physiological functions of pathogenic fungi, such as nutrient sensing, stress response, and cell cycle progression. Given their robust immunosuppressant and anti-tumor activities, TOR inhibitors are widely used in clinical settings. In the present study, a microdilution checkerboard-based approach was employed to assess interactions between the oral mTOR inhibitor everolimus (EVL) and antifungal agents when treating Aspergillus species derived from 35 clinical isolates in vitro. The results revealed that EVL exhibited promising inhibitory synergy with itraconazole (ITC), posaconazole (POS), and amphotericin B (AMB) for 85.7%, 74.2%, and 71.4%, respectively. In contrast, EVL exhibited minimal synergistic inhibitory activity when applied together with voriconazole (VRC, 14.3%). Antagonistic interactions were not observed. In vivo experiments were conducted in G. mellonella, revealed that EVL in combination with EVL improved the larvae survival rates in the ITC, VRC, POS and AMB groups by 18.3%, 13.3%, 26.7% and 13.3%, respectively. These data suggest that combination treatment with EVL and antifungal agents have hold promise as a means of alleviating clinical aspergillosis.